The Role of Institutional Quality in Renewable Energy Transition: A Panel CS-ARDL Analysis of MIKTA countries - Shanyazov, Nuriddin; Madrakhimov, Kakhramon; Matkarimov, Mansur; Sattarova, Mahfuza; Makhmudov, Samariddin; Kushmanov, Jasur (International Journal of Energy Economics and Policy, 2026)
This study investigates the role of institutional quality in driving the renewable energy transition in MIKTA countries (Mexico, Indonesia, Republic of Korea, Türkiye, and Australia) over the period 2000–2023. Second-generation panel econometric techniques are employed to address slope heterogeneity and cross-sectional dependence, as confirmed by Pesaran CD and slope homogeneity tests. The analysis applies the Cross-Sectionally Augmented ARDL (CS-ARDL) approach alongside the Westerlund cointegration test to establish a stable long-run relationship among the variables. Long-run results reveal that institutional quality significantly enhances renewable energy consumption per capita. Specifically, a one-unit increase in Control of Corruption raises renewable energy use by approximately 2.34%, while Political Stability increases it by 1.63%. Economic growth also exerts a positive influence, with a GDP per capita elasticity of 0.87. Short-run dynamics indicate a significant error correction term (−0.372), implying that 37.2% of deviations from long-run equilibrium are corrected annually. Robustness checks using CCEMG and AMG estimators confirm the consistency of the findings. Overall, the results underscore the critical importance of institutional reforms in fostering renewable energy investment and achieving sustainable development in MIKTA economies.